SIGNIFICANCE OF SEMANTIC WEB - PITFALLS AND BENEFITS OF USE IN THE COMMON JUDICIARY - ODLANICKA-POCZOBUTT, Monika (Comparative Legilinguistics, 2019)
Semantic Webs increasingly allow the processing of information over the Internet according to their content and purpose. The widespread use of metadata standards has, however, caused interoperability problems between different systems. Enabling users to search for different languages requires translation resources to cross the language barrier can be a serious challenge. The presented tendency to use semantic webs is an opportunity for legislation, facilitating the process of developing and providing legal regula-tions and managing the progress of legislative work and implementation of procedures. The aim of this article is to review semantic web theory in rela-tion to the pitfalls of defining and applying ontology to the machine-based understanding of content stored in the network. The scope of this article is a preliminary analysis of aspects of interdisciplinary cooperation in the metadata creation phase - indexed according to the conceptual analysis (ontology) of a given field. The area of research interest was also the benefits and pitfalls of using open source, XML and the Legal Semantic Web in the common judiciary.